Handbook of procurement - Dimitri, Nicola; Piga, Gustavo 1964-; Spagnolo, Giancarlo (Cambridge University Press, 2006)
How can organizations ensure that they can get best value for money in their procurement decisions? How can they stimulate innovations from their dedicated suppliers? With contributions from leading academics and professionals, this 2006 handbook offers expert guidance on the fundamental aspects of successful procurement design and management in firms, public administrations, and international institutions. The issues addressed include the management of dynamic procurement; the handling of procurement risk; the architecture of purchasing systems; the structure of incentives in procurement contracts; methods to increase suppliers' participation in procurement contests and e-procurement platforms; how to minimize the risk of collusion and of corruption; pricing and reputation mechanisms in e-procurement platforms; and how procurement can enhance innovation. Inspired by frontier research, it provides practical recommendations to managers, engineers and lawyers engaged in private and public procurement design